Proceedings of the Ocean Drilling Program 1996
DOI: 10.2973/odp.proc.sr.147.016.1996
|View full text |Cite
|
Sign up to set email alerts
|

Petrologic and Stable Isotope Constraints on Hydrothermal Alteration and Serpentinization of the EPR Shallow Mantle at Hess Deep (Site 895)

Abstract: Leg 147 of the Ocean Drilling Program recovered sections of the East Pacific Rise lower crust and shallow mantle ( l Ma), tectonically exposed at the western end of the Cocos-Nazca propagator of the Hess Deep Rift Valley. These rocks record a polyphase history of hydrothermal alteration and provide new constraints on the depth and mechanisms of hydrothermal circulation at fast-spreading ridges. A complex sequence of harzburgite-dunite-troctolite-gabbro recovered at Site 895 is considered to be the result of pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
120
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 73 publications
(130 citation statements)
references
References 70 publications
(124 reference statements)
10
120
0
Order By: Relevance
“…Most of the oxygen-isotope studies of oceanic serpentinized peridotites to date have suggested lower temperatures of serpentinization (70°-250°C; Wenner and Taylor, 1971;Sheppard, 1980;Bonatti et al, 1984). However, high temperatures of serpentinization, similar to those calculated in this paper, have recently been reported from the Hess Deep ultramafic exposures (East Pacific Rise; Agrinier et al, 1995;Früh-Green et al, 1996).…”
supporting
confidence: 75%
See 4 more Smart Citations
“…Most of the oxygen-isotope studies of oceanic serpentinized peridotites to date have suggested lower temperatures of serpentinization (70°-250°C; Wenner and Taylor, 1971;Sheppard, 1980;Bonatti et al, 1984). However, high temperatures of serpentinization, similar to those calculated in this paper, have recently been reported from the Hess Deep ultramafic exposures (East Pacific Rise; Agrinier et al, 1995;Früh-Green et al, 1996).…”
supporting
confidence: 75%
“…The corresponding oxygen-isotope fractionations, Δ 1 ^serpentine-magnetite), are small (between 5.1%o and 3.8%o), and are lower than the previously published values for oceanic serpentinized peridotites (above 9.5%e; Wenner and Taylor, 1973) but are similar to those measured in Hess Deep serpentinized peridotites (Früh-Green et al, 1996;Agrinier et al, 1995). Although the…”
Section: Oxygen-isotope Fractionation Between Serpentine and Magnetitesupporting
confidence: 54%
See 3 more Smart Citations